Spherical tiling with GeoGebra - Breda, Ana (2019)
The theory of spherical tilings is an interesting and fruitful field, attracting, among other researchers, mathematicians. It is a transverse topic crossing several mathematical areas such as geometry, algebra, topology and number theory, but it is also an object of interest for other scientific fields such as chemistry, physics, art and architecture. Here, we make use of GeoGebra to establish some results, describing a class of monohedral spherical tilings and inferring some conjectures. This will highlight how the use of this software has been crucial for the construction of new knowledge in mathematics with applications in different areas of engineering.